Pengaruh Gaya Kepemimpinan, Komunikasi, Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan Pada PT Kurnia Luwuk Sejati Pabrik Minyak Kelapa Sawit Toili: The Influence of Leadership Style, Communication, and Work Environment on Employee Work Morale at PT Kurnia Luwuk Sejati Toili Palm Oil Factory - Sri Mulyaningsih Kamaru; Narti (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
The formulation of the problem in this study is how leadership style, communication, and work environment have a significant effect on employee work enthusiasm partially and simultaneously at PT Kurnia Luwuk Sejati. The type of data is qualitative which is quantified with a sample of 55 respondents. The analysis tool is Multiple Linear Regression Test with the equation form Y = 7.715 - 0.123 - 0.291 + 0.424, correlation coefficient, determination coefficient, t test and f test. The correlation coefficient is 50.9% and the remaining 49.1% shows a fairly strong relationship. The determination coefficient is 25.9% and the remaining 74.1% is influenced by other variables studied. The results of the t test are the calculated T value of leadership style of -0.549 with a significance level of 0.585, communication of 1.128 with a significance level of 0.265, and the work environment of 2.750 with a significance level of 0.008. The T table is 1.675 (t count > t table). The F test result is 5.934, the F table is 3.18, so there is a significant influence between Leadership Style (X1), Communication (X2), Work Environment (X3), and Work Spirit (Y).